The effect of highly active antiretroviral therapy on Human Papilloma Virus Infection and Cervical Dysplasia in women living with HIV - Zeier, Michele D. (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.